Balloon-occluded retrograde transvenous obliteration of gastric varix with multiple drainage veins performed with temporal occlusion of the pericardiacophrenic vein with a micro-balloon. (25th August 2015) - Yamagami, Takuji; Iida, Makoto; Tanitame, Nobuko; Yoshimatsu, Rika; Ono, Chiaki; Waki, Koji; Tsuji, Keiji; Awai, Kazuo
We encountered a case with a gastric varix that drained into the gastro-renal shunt, left pericardiacophrenic vein, and several other dilated collateral veins. This patient had a circumaortic venous ring. For this case we successfully performed balloon-occluded retrograde transvenous obliteration in which sclerotic agents were infused from the balloon catheter advanced to the left pre-aortic renal vein and the tip was wedged into the end of the gastro-renal shunt. Before injection of sclerotic agents, collateral veins other than the left pericardiacophrenic vein were embolized with micro-coils. During the injection, the left pericardiacophrenic vein was occluded temporarily with a micro-balloon catheter coaxially advanced from the catheter inserted from the femoral vein to the left pericardiacophrenic vein through the left brachiocephalic vein.